Study to Assess Attitudes Towards Sensitive Messages in Pakistan - World Bank (Washington, DC, 2014)
The objective of this study is to comprehend decision making processes and attitudes related to discussion on television and other mass media of condoms and other sensitive issues, by performing comprehensive research including (i) a review of available literature; (ii) focus group meetings with decision-makers involved in behavior change communications in Pakistan (staff of the Ministry of Health, National and Provincial AIDS Control Programmes, Ministry of Population Welfare; officials working in television and radio, and censor board members); and (iii) focus group meetings with a sample of the general population in urban and rural areas of Pakistan. This paper includes the following headings: executive summary, background of the study literature review findings, focus group research findings, and recommendations.